THERAPEUTIC INVESTIGATION OF ANTIMICROBIAL PROPERTIES OF WITHANIA SOMNIFERA, TERMINALIA ARJUNA, BACOPA MONNIERI, RANUNCULUS SCELERATUS AND ACALYPHA INDICA. - Debanjana Prasad, Shailesh Solanki (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The present work was carried out using root parts of five medicinal plants from interior areas of Agrakhal of Uttrakhand and surajpur of Uttar Pradesh, India in order to collect the information of these medicinal plants used traditionally. The objective of this work was to investigate and compare, phytochemical analysis, qualitatively, antimicrobial screening activity of root extractsof Withania somnifera, Terminalia arjuna, Bacopa monnieri, Ranunculus sceleratus andAcalypha indicaby using solvents Ethanol, Methanol and Chloroform. In Qualitative Analysis, major active compounds were determined. Antimicrobial screening including Minimum Inhibitory Concentration was evaluated by Disc Diffusion method with four standard antibacterial agents Ciprofloxacin, Tobramycin, Streptomycin, Azithromycin and two standard antifungal agents Fluconazole, Itraconazole. Qualiitative Screening results showed, high presence of beneficial active compounds including alkaloids, coumarin, flavonoids, phenols, tannins in ethanol and methanol extracts. Disc Diffusion Assay revealed maximum potential antimicrobial activity at concentration 10mg/ml against microbes Bacillus subtilis(MTCC 441):18mm-24.9mm, Staphylococcus aureus(MTCC 96):17mm-19.9mm, Pseudomonas aeruginosa (MTCC 647):16mm-18.3mm, Acinetobactorbaumanni(MTCC 1425):17.1mm-27.1mm, Saccharomyces cerevisiae(MTCC 250):15.9mm-22.2mmand Aspergillus niger(MTCC 9652):14.8mm-20.3mm were exhibited by these extracts. The MIC was carried out at different concentrations (10mg/ml, 5mg/ml, 2.5mg/ml, 1.25mg/ml, 0.0625mg/ml). The MIC values of ethanolic and methanolic root extracts were noted to have better function at low MIC values started at 0.625mg/ml against bacteria and 1.25mg/ml against fungi and yeast, respectively as compared with standard agents. It was reported, these ethanol-methanol root extractsare highly effective the for high potential medicinal properties